The determination of accretion rate in Setiu Mangrove, Malaysia: Thorium-230 versus artificial horizontal marker method - B. Y., Kamaruzzaman; H., Mohd Lokman; I., Sulong; S., Hasrizal (Universiti Putra Malaysia Press, 2003)
In this study, determination of sediment accretion rate using the 230Th and the artificial horizon marker method in Setiu mangrove were done. Applying the 230Th excess method, an average accretion rate of 0.62 cm yr1 was obtained. This is comparable to that of an artificial horizon marker method giving an average of 0.61 cm yr1• The 230Th method provides a rapid and simple method of evaluating 230Th accumulation histories in sediment cores. Sample preparation is also significantly simplified, thus providing a relatively quick and easy method for the determination of the accretion rate in mangrove areas. Assuming that the accretion rate values are accurate, this may imply that the sediments in the upper 100 cm were deposited during the last 163 years.